Adsorptive Removal of As(III) from Aqueous Solution - Bhattarai, Pushpa; Bohra, Khagendra Prasad; Pokhrel, Megh Raj (Journal of Institute of Science and Technology, 2015)
The iron-modified Dalbergia sissoo sawdust was synthesized by loading iron (III) onto phosphorylated Dalbergia sissoo sawdust via soaking in a ferric salt solution. Batch studies were performed at an initial concentration of 1 mg/l to evaluate the effect of parameters such as pH, equilibrium time, adsorbent dose and concentration of adsorbate. Kinetics and isotherm modeling studies demonstrated that the experimental data best fit a pseudo-first order and Langmuir isotherm model, respectively. The maximum adsorption capacity was found to be 1.33 mg/g for As(III) onto FePDSD suggesting the suitability of chemically modified Dalbergia sissoo sawdust for the adsorptive removal of As(III) from aqueous solution. Journal of Institute of Science and Technology, 2014, 19(1): 150-154